The International Union of Social Studies of Malines and the Catholic Cultural Turn: Drafting a Moral Code at the End of the Constantinian Era - Bosschaert, Dries (Church history and religious culture, 2019)
The present article argues that the unexpected end of the Union de Malines' Code de morale culturelle, an international collaboration of prominent twentieth-century Catholic moral theologians, should be attributed to three shifts in Catholic Social Teaching, only the first two of which the Union de Malines managed to undergo: from scholastic hegemony to theological diversity, from social doctrine to personalism, and from a juridical style of writing to a humanistic one. Particularly this last shift, introduced by the Second Vatican Council, proved to be a too big a leap for the Union, understood as a little social tradition,' to take. The cultural turn, which the Union de Malines had in fact anticipated, proved by the end of the council to belong to the future.